SPOLOČENSKÝ A PRÁVNY KONTEXT PODNIKATEĽSKEJ ETIKY - Marinicová, Mária (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Мария Мариничева. Социальный и правовой контекст деловой этики. Этика в бизнесе, также как и во всех областях жизни, становится все более и более жизненной в современном обществе. Статья настраивает интуитивно на общепринятое предположение, что принципы деловой этики приводят в конечном счете к более эффективной экономической системе, основанной на прибыльности. Вторичная цель и амбиция этой статьи – выделить некоторые правовые аспекты в контексте деловой этики. Без этики, без уважения для индивидуума и уважения основных прав гарантированных в Основном Законе Государства (Конституция), не может ожидать успеха даже в экономической жизни. Ключевые слова: экономика, закон, деловая этика, корпоративная ответственность, этика, управление, моральный кодекс. Mária Marinicová. Social and legal context of business ethics. Ethics in business, as well as in all areas of life, is becoming increasingly vital in contemporary society. Article builds on the intuitive, but generally-accepted assumption that the principles of business ethics leads ultimately, in the long term, to more efficient economic system based on profitability. A secondary aim and ambition of this article is to highlight some legal aspects in the context of business ethics. Without ethics, respect for the individual and respect for the fundamental rights guaranteed in the Basic Law of the State (Constitution), can not expect success even in economic life. Keywords: economics, law, business ethics, corporate responsibility, morality, management, code of ethics.